Personalization of treatment based on obesity phenotypes - Maria Witkowska; Karolina Błaszczak; Joanna Skotnicka; Kamila Podgórniak; Marlena Cąkała; Magdalena Kozioł; Julia Piotrowska; Katarzyna Lenczewska; Kinga Klimczak; Aleksandra Zajkowska (Kazimierz Wielki University, 2024)
Introduction: Obesity is a significant clinical problem worldwide. The disease exhibits remarkable heterogeneity, leading to diverse pathogenesis among individuals. Despite a growing selection of weight-reducing medications and increased awareness of the importance of a healthy lifestyle, the effectiveness of obesity therapy often remains insufficient. This raises the question of whether tailoring obesity pharmacotherapy to specific phenotypes and individual patient characteristics results in improved treatment outcomes. Objective: To review literature on the effectiveness of obesity treatment based on the personalization of pharmacotherapy according to its underlying causes. Current Knowledge: Currently, the early outcome of weight loss is closely linked to the long-term effectiveness of obesity pharmacotherapy. However, due to the diversity of obesity pathogenesis, it is not helpful in selecting therapy at the initiation of treatment. Specific characteristics are sought to indicate the appropriate drug during therapy planning. In a U.S. study (Acosta et al., 2021) results showed that phenotype-guided obesity pharmacotherapy resulted in clinically more significant absolute weight loss than in the non-phenotyped group. Other studies demonstrated that for very rare types of obesity dependent on specific genetic mutations, targeted treatment addressing these defects yielded the best therapeutic outcomes (recombinant human leptin therapy for patients with leptin gene mutation - Farooqi et al., 2002; setmelanotide therapy for individuals with proopiomelanocortin deficiency - Clément et al., 2020). The impact of specific gene variants on therapeutic response should also be considered, leading to variability in treatment effects for different patients using the same drug. Conclusion: The concept of basing therapy on obesity phenotypes may currently serve as a guide for treatment selection, although it still requires confirmation in randomized clinical trials.